2005
DOI: 10.1017/s0954102005002865
|View full text |Cite
|
Sign up to set email alerts
|

Late Miocene vegetation and palaeoenvironments of the Drygalski Formation, Heard Island, Indian Ocean: evidence from palynology

Abstract: Well sorted, fine lithic sandstone within the Drygalski Formation at Cape Lockyer on the southern tip of Heard Island, preserves a diverse terrestrial palynoflora as well as marine diatoms and a few foraminifera. A combination of these elements suggests a Late Miocene age (10–5 Ma). The palaeovegetation was markedly different from that presently on the island, and appears to comprise at least two ecologically distinct communities: open heath or herbfield dominated by grasses and Asteraceae, and a more mesophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…Mildenhall (1989) also recorded several similar specimens in the lower part of the CIROS-1 sequence, but regarded these specimens as contamination. However, Truswell et al (2005) recorded Asteraceae-Poaceae dominated palynofloras in the late Miocene Drygalski Formation of Heard Island. Asteraceae pollen grains may represent drier environments, as in the late Miocene of Heard Island (Truswell et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mildenhall (1989) also recorded several similar specimens in the lower part of the CIROS-1 sequence, but regarded these specimens as contamination. However, Truswell et al (2005) recorded Asteraceae-Poaceae dominated palynofloras in the late Miocene Drygalski Formation of Heard Island. Asteraceae pollen grains may represent drier environments, as in the late Miocene of Heard Island (Truswell et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…During the Miocene, the sedimentation became homogenous with the deposition of nannofossil-and foraminifer-bearing pelagic oozes at sites 1140 and 1138, foraminifer-bearing shales at site 1139 and diatom/foraminifer-bearing shales at site 737. At Heard Island, the late Miocene-Pliocene interval corresponds to volcanic marine sediments including lithic sandstones revealing both terrestrial palynoflora and marine diatoms and a few foraminifera (Quilty and Wheller, 2000;Truswell et al, 2005). Important hiatuses are recorded in the Lower Miocene (23-19 Ma) at sites 736 and 1138 and in the Late Miocene even Pliocene (14-3 Ma) at sites 1139 and 1140.…”
Section: The North and Central Kerguelen Plateaumentioning
confidence: 99%
“…The results of the Drakkar dredges (Frö lich et al, 1983) are also indicated in the figures. Descriptions of samples on-shore Kerguelen Islands are from Nougier (1970);Nougier (1970), and on Heard Island, descriptions come from Quilty et al (1983), Quilty and Wheller (2000) and Truswell et al (2005).…”
Section: The North and Central Kerguelen Plateaumentioning
confidence: 99%
“…Tropical rainforest-like environments with diverse angiosperms were present by 100 Ma and the previously dominant gymnosperm, cycadophytes and free-sporing lineages were rapidly declining (Couvreur et al 2011). From the early Mesozoic to middle Cretaceous, polar forests and woodlands (the Austral conifer forest) dominated the Antarctic continent adjacent to which was the landmass that was to become Zealandia (Truswell et al 2005;Leppe et al 2012). Araucariceae and Podocarpaceae trees formed a gymnosperm overstorey above a subcanopy of ferns and fern allies.…”
Section: Originsmentioning
confidence: 99%